2015
DOI: 10.1134/s1070363215080204
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic and chromato–mass spectral characterization of amino acids derivatives formed via the interaction with dimethyl acetal of dimethylformamide

Abstract: A series of amino acids have been converted into the derivatives via interaction with dimethylformamide dimethyl acetal for gas chromatography identification. The derivatives have been for the first time characterized with mass spectra and retention indices corresponding to the standard nonpolar polydimethylsiloxane stationary phases. Basic features of mass spectroscopic fragmentation of the derivatives have been stated; the rules for interpretation of their gas chromatography retention indices have been figur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…[2] and 1143 i.u. [21] were reported for methyl ester of N-dimethylaminomethylene-alanine and both publications indicated that glycine did not form such a derivative at standard conditions; it can be explained by specific chemical properties of glycine as the first member of the homologous series.…”
Section: Resultsmentioning
confidence: 99%
“…[2] and 1143 i.u. [21] were reported for methyl ester of N-dimethylaminomethylene-alanine and both publications indicated that glycine did not form such a derivative at standard conditions; it can be explained by specific chemical properties of glycine as the first member of the homologous series.…”
Section: Resultsmentioning
confidence: 99%